KARAKTERISTIK COOKIES MOCAF DENGAN SUBSTITUSI AMPAS KACANG HIJAU DAN PENAMBAHAN ISOLAT SOY PROTEIN [CHARACTERISTICS OF MOCAF COOKIES WITH SUBSTITUTION OF MUNG BEAN DREGS AND ADDITION OF SOY PROTEIN ISOLATE] - Titri Siratantri Mastuti (Universitas Pelita Harapan, 2023)
Cookies are a type of biscuit that is widely consumed by all with characteristics of being dense with a crunchy texture. Food diversification is needed to reduce dependency on imported wheat. The use of wheat flour as the main raw material for cookies can be replaced using flour from local Indonesian ingredients such as mocaf (modified cassava). However, the low protein content and the absence of glutein in mocaf can affect the texture of the cookies. Mung bean dregs and Soy Protein Isolate (ISP) can be used as a source of protein and improving the characteristics of mocaf cookies. The content of fiber and iron in mung bean dregs can improve the functional properties of cookies. The purpose of this study was to determine the best ratio between mung bean dregs and mocaf flour and ISP's concentration on producing mocaf cookies with the best characteristics. The research consists of the preliminary stage and the main stage. The preliminary stage is characterization of mung bean dregs. The main stage is the manufacture of mocaf cookies with factors are the ratio of mocaf flour (TM) with mung bean dregs flour (ASKH), and concentration of ISP. The results showed that the best cookies were obtained from cookies with a TM:ASKH ratio of 50:50 and an ISP of 15%. Mocaf cookies with the addition of mung bean dregs and ISP had a moisture content of 3.54 ± 12.92 %, protein 7.43 ± 14.25 %, fat 21.40 ± 1.54 %, ash 1.76 ± 1.53 %, carbohydrate 65.45 ± 0.61, iron 1.39 ± 1.51 mg/100 g, dietary fiber 11.45 ± 0.37 %, hardness 1418.49 ± 0.39 gf, kamba density 0.31 ± 1.19 g/mL. The content of water, protein, ash and fat from mocaf cookies can meet the quality standards of cookies' SNI. The selected cookies has a slightly yellow color with a slightly hard texture, a bit flavorful, taste of mung beans and rich in fiber.Bahasa Indonesia Abstract:Cookies merupakan salah satu jenis biskuit yang banyak dikonsumsi semua lapisan masyarakat dengan ciri khasnya memiliki tekstur padat namun renyah. Penggunaan tepung terigu sebagai bahan baku utama cookies dapat digantikan menggunakan tepung dari bahan lokal Indonesia seperti mocaf (modified cassava). Namun kadar protein yang rendah dan ketiadaan glutein pada mocaf dapat memengaruhi tekstur cookies. Ampas kacang hijau dan Isolat Soy Protein (ISP) dapat digunakan dalam pembuatan cookies sebagai sumber protein dan memperbaiki karakteristik cookies mocaf. Kandungan serat dan zat besi pada ampas kacang hijau dapat meningkatkan sifat fungsional cookies. Tujuan dari penelitian ini adalah menentukan rasio terbaik antara ampas kacang hijau dan tepung mocaf serta konsentrasi ISP untuk menghasilkan cookies mocaf dengan karakteristik terbaik. Penelitian terdiri dari tahap pendahuluan dan tahap utama. Tahap pendahuluan dilakukan karakterisasi ampas kacang hijau. Tahap utama dilakukan pembuatan cookies mocaf dengan faktor perlakuan rasio substitusi tepung mocaf (TM) dengan tepung ampas kacang hijau (ASKH) serta variasi konsentrasi penambahan ISP. Hasil penelitian menunjukan cookies terbaik diperoleh dari cookies dengan rasio TM:ASKH 50:50 dan konsentrasi ISP 15%. Cookies mocaf dengan penambahan ampas kacang hijau dan ISP memiliki kadar air sebesar 3,54 ± 12,92 %, protein 7,43 ± 14,25 %, lemak 21,40 ± 1,54 %, abu 1,76 ± 1,53 %, karbohidrat 65,45 ± 0,61, zat besi 1,39 ± 1,51 mg/100 g, serat pangan 11,45 ± 0,37 %, hardness 1418,49 ± 0,39 gf, densitas kamba 0,31 ± 1,19 g/mL. Cookies terpilih memiliki warna agak kuning dengan tekstur agak keras, agak beraroma dan berasa kacang hijau.